Characterization of antigens of hookworm larvae (Ancylostoma spp.) - Sri Sumarni, Sri Sumarni (Universitas Gadjah Mada, 1992)
Cutaneous larva migrans (CLM) is caused by animal hookworm larvae in man. The conventional diagnosis and treatment of CLM will injure the skin of the patients, and the results are not satisfying. Therefore it should be necessary to do the serological test to diagnose CLM.The antigens were prepared by extracting the hookworm larvae in CTAB detergent, and injected into Balb/C mice. Characterization of antigens were done, quantitatively (by spectrophotonieter) and qualitatively (by SDS PAGE electrophoresis).The results showed that the titre rate of hookworm larvae antigens was 145 ug/ml. The antigens consist of 4 protein fractions with molecular weight of 25 KD, 55 KD, 66 KD and above 66 KD. Those antigents apparently generated high immune response in immunized miceKey Words; Ancylostoma spp. - CTAB detergent - SDS PAGE electrophoresis - immunology - parasitology